Liquid metal graphene thermal conductive gasket and method of making same

CN122909813APending Publication Date: 2026-10-13SINGLETON (CHANGZHOU) MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611052909.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本申请的目的在于提供一种液态金属石墨烯导热垫片及其制备方法,以解决现有技术中的石墨烯导热垫片存在的表面石墨烯粉体易脱落、垫片垂直于石墨烯片层排列方向的拉伸强度极低、低熔点液态金属易暴露于垫片表面引发电化学腐蚀与金属脆化现象的技术问题

Benefits of technology

[0037]本申请导热垫片包括沿第一方向堆叠的第一石墨烯泡棉层以及沿第二方向堆叠的第二石墨烯泡棉层,且石墨烯泡棉内部填充并固化有硅胶,形成纵横交错的多维度的三维支撑网络,使垫片在面内各方向均具备优异的力学强度,解决了传统石墨烯导热垫片在垂直于片层排列方向力学强度极低的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909813A_ABST
    Figure CN122909813A_ABST
Patent Text Reader

Abstract

The application discloses a liquid metal graphene heat-conducting gasket and a preparation method thereof. The heat-conducting gasket comprises a heat-conducting base body and a high-melting-point liquid metal layer arranged on and combined with two side surfaces of the heat-conducting base body in the thickness direction. The heat-conducting base body comprises first graphene foam layers and composite layers which are alternately and sequentially stacked along a first direction. The composite layers comprise second graphene foam layers and low-melting-point liquid metal layers which are alternately and sequentially stacked along a second direction. The first graphene foam layers, the second graphene foam layers and the low-melting-point liquid metal layers are integrally bonded through a silica gel base body. The silica gel base body is filled in internal pores and interlayer gaps of the first graphene foam layers and the second graphene foam layers. The heat-conducting gasket has excellent mechanical strength in each direction in the plane, avoids the problem of electrochemical corrosion caused by liquid metal leakage, improves the interfacial bonding strength and guarantees the heat-conducting performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of thermal pad technology, specifically relating to a liquid metal graphene thermal pad and its preparation method. Background Technology

[0002] With the continuous increase in the integration and power density of electronic components, the heat generation per unit area has increased dramatically. Efficient heat dissipation has become a core bottleneck restricting the performance release and long-term operational reliability of electronic devices. As a core component that fills the microscopic air gap between heat-generating devices and heat dissipation structures and reduces contact thermal resistance, the thermal conductivity, mechanical properties, and environmental stability of thermal interface materials directly determine the overall efficiency of the heat dissipation system.

[0003] Graphene, with its extremely high in-plane thermal conductivity, low density, and excellent chemical stability, has become one of the core research directions for high thermal conductivity interface materials. Current technologies mostly employ graphene foam and oriented stacked graphene films to prepare thermal pads, relying on the oriented arrangement of graphene to achieve excellent thermal conductivity. However, existing graphene thermal pads still have several significant drawbacks: 1. Graphene powder on the pad surface is prone to detachment, which can easily cause short circuits and reduced insulation performance, threatening the operational safety of electronic devices; 2. The mechanical properties of the pads exhibit significant anisotropy, with extremely low tensile strength perpendicular to the graphene sheet alignment direction. Some products have a tensile strength of only about 0.05 MPa in this direction, making them prone to cracking and breakage, and their service life is difficult to guarantee.

[0004] To further improve the vertical thermal conductivity of graphene thermal pads, the industry has proposed a technical solution that combines liquid metal with graphene. This utilizes the excellent intrinsic thermal conductivity and interfacial wettability of liquid metal to fill the internal pores and interlayer gaps of graphene, creating a more continuous thermal conductivity pathway. However, existing graphene-liquid metal composite pads also have several technical drawbacks: 1. Poor interfacial bonding reliability: The significant differences in properties between graphene and liquid metal, coupled with mismatched thermal expansion coefficients, make it prone to delamination and separation of the liquid metal and graphene layers under long-term thermal cycling conditions. This leads to a significant increase in interfacial thermal resistance and a rapid decline in heat dissipation performance. 2. To improve the interfacial bonding strength between liquid metal and graphene, existing technologies often use low-melting-point liquid metal to directly penetrate the internal pores of graphene. In this approach, the low-melting-point liquid metal is easily exposed on the pad surface. Upon contact with the metal electrodes or pads of chips or heat sinks, it can easily cause electrochemical corrosion and metal embrittlement, resulting in serious problems such as chip pin corrosion and breakage, and interfacial contact failure. Summary of the Invention

[0005] The purpose of this application is to provide a liquid metal graphene thermal pad and its preparation method, so as to solve the technical problems of existing graphene thermal pads, such as easy shedding of surface graphene powder, extremely low tensile strength of the pad perpendicular to the graphene sheet arrangement direction, and easy exposure of low melting point liquid metal on the pad surface, which causes electrochemical corrosion and metal embrittlement.

[0006] To achieve the above objectives, the first aspect of this application provides a liquid metal graphene thermal pad, including a thermally conductive substrate and a high-melting-point liquid metal layer covering and bonded to both sides of the thermally conductive substrate in the thickness direction.

[0007] The thermally conductive substrate includes a first graphene foam layer and a composite layer that are alternately stacked along a first direction. The composite layer includes a second graphene foam layer and a low-melting-point liquid metal layer that are alternately stacked along a second direction. The first graphene foam layer, the second graphene foam layer, and the low-melting-point liquid metal layer are bonded together by curing with a silicone matrix. The silicone matrix fills the internal pores and interlayer gaps of the first graphene foam layer and the second graphene foam layer.

[0008] Wherein, the first direction is perpendicular to the thickness direction of the thermally conductive substrate, the second direction is perpendicular to the thickness direction of the thermally conductive substrate, and an angle is formed between the first direction and the second direction.

[0009] In one or more embodiments, the melting point of the high-melting-point liquid metal layer is 115~125°C.

[0010] In one or more embodiments, the melting point of the low-melting-point liquid metal layer is 60~70°C.

[0011] In one or more embodiments, the outermost part of the thermally conductive substrate in the first direction is the first graphene foam layer.

[0012] In one or more embodiments, the outermost part of the composite layer in the second direction is the second graphene foam layer.

[0013] In one or more embodiments, the thickness of the thermally conductive substrate is 180~220μm, and the thickness of the high-melting-point liquid metal layer is 20~50μm.

[0014] In one or more embodiments, in the first direction, the first graphene foam layer has an extension length of 380~420μm, and the composite layer has an extension length of 80~120μm.

[0015] In one or more embodiments, in the second direction, the extension length of the second graphene foam layer is 380~420μm, and the extension length of the low-melting-point liquid metal layer is 80~220μm.

[0016] To achieve the above objectives, a second aspect of this application provides a method for preparing the liquid metal graphene thermal pad described in any of the above embodiments, comprising:

[0017] Graphene foam and low-melting-point liquid metal sheets are alternately stacked in a mold;

[0018] The silicone curing liquid is infiltrated into the graphene foam;

[0019] The mold is heated to melt the low-melting-point liquid metal sheet and to solidify the silicone curing liquid to form a silicone matrix, thereby obtaining a first graphene liquid metal block;

[0020] The first graphene liquid metal block was removed and cut along its stacking direction to obtain a graphene liquid metal sheet;

[0021] Graphene foam and the graphene liquid metal sheet are alternately stacked in a mold;

[0022] The silicone curing liquid is infiltrated into the graphene foam;

[0023] The mold is heated to melt the low-melting-point liquid metal sheet and to solidify the silicone curing liquid to form a silicone matrix, thereby obtaining a second graphene liquid metal block;

[0024] The second graphene liquid metal block is removed and cut along its stacking direction to obtain the thermally conductive substrate;

[0025] High-melting-point liquid metal sheets are covered on both sides of the thermally conductive substrate in the thickness direction. The high-melting-point liquid metal sheets are heated to melt, pressed together, and then cooled to obtain the liquid metal graphene thermally conductive pad.

[0026] In one or more embodiments, the silicone curing liquid comprises the following components: vinyl silicone oil, end-hydrogen silicone oil, side-hydrogen silicone oil, carboxyl silicone oil, platinum-coated catalyst, and titanate coupling agent;

[0027] The platinum-coated catalyst is a platinum catalyst encapsulated in a phase change material, so that the platinum catalyst can be released when the phase change material melts and catalyze the addition curing reaction of silicone oil.

[0028] In one or more embodiments, the step of heating the mold includes:

[0029] The mold is heated to a first temperature, which melts the low-melting-point liquid metal sheet and partially penetrates into the adjacent graphene foam. The first temperature is lower than the melting point of the phase change material.

[0030] The mold is heated to a second temperature to solidify the silicone curing liquid and form a silicone matrix. The second temperature is greater than the melting point of the phase change material.

[0031] In one or more embodiments, the phase change material has a melting point of 78~82°C, the first temperature is 65~75°C, and the second temperature is 100~130°C.

[0032] In one or more embodiments, the phase change material is paraffin.

[0033] In one or more embodiments, the silicone curing liquid comprises the following components in parts by weight: 78-82 parts vinyl silicone oil, 8-12 parts end-hydrogen silicone oil, 3-7 parts side-hydrogen silicone oil, 2-4 parts carboxyl silicone oil, 0.3-0.6 parts platinum-coated catalyst, and 1-2 parts titanate coupling agent.

[0034] In one or more embodiments, the step of infiltrating the silicone curing liquid into the graphene foam includes: immersing the mold in the silicone curing liquid and performing a vacuum treatment on the inside of the mold to allow the graphene foam to fully absorb the silicone curing liquid.

[0035] In one or more embodiments, the density of the graphene foam is 0.15~0.25 g / cm³. 3 .

[0036] The advantages of this application, which differ from existing technologies, are:

[0037] The thermal pad of this application includes a first graphene foam layer stacked along a first direction and a second graphene foam layer stacked along a second direction. The graphene foam is filled with and cured with silicone to form a crisscrossing multi-dimensional three-dimensional support network, which enables the pad to have excellent mechanical strength in all directions in the plane, and solves the problem of extremely low mechanical strength of traditional graphene thermal pads in the direction perpendicular to the arrangement of the sheets.

[0038] The low-melting-point liquid metal layer of the thermal pad in this application is encapsulated inside the thermally conductive substrate and stacked with the second graphene foam layer in a direction perpendicular to the thickness direction to form a composite layer. This effectively avoids the electrochemical corrosion problem caused by leakage of low-melting-point liquid metal. At the same time, the low-melting-point liquid metal layer encapsulated inside can form vertical thermal conduction channels at various points on the thermal pad, effectively ensuring the vertical thermal conductivity of the thermal pad.

[0039] The surface of the thermal pad in this application is in contact with electronic components such as chips and heat sinks through a high melting point liquid metal layer, and the graphene foam is filled with and cured with a silicone matrix, which effectively avoids the problem of short circuit caused by graphene powder falling off, and effectively ensures the thermal conductivity of the thermal pad.

[0040] This application significantly improves the bonding strength between the low-melting-point liquid metal and the graphene foam by curing and bonding the first graphene foam layer, the second graphene foam layer and the low-melting-point liquid metal layer with a silicone substrate. This avoids the problem of increased interfacial thermal resistance caused by the delamination of liquid metal and graphite, and helps to improve service life and thermal conductivity.

[0041] This application effectively improves the interfacial bonding strength between graphene and liquid metal by introducing carboxyl silicone oil and titanate coupling agent into the components of the silicone curing liquid, thereby increasing the service life and operational stability of the thermal pad. By introducing a platinum-coated catalyst to precisely control the curing process, it helps to enhance the bonding strength between the low-melting-point liquid metal and graphene. Attached Figure Description

[0042] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0043] Figure 1 This is a schematic diagram of one embodiment of the liquid metal graphene thermal conductive pad of this application;

[0044] Figure 2 This is a schematic diagram of the structure of one embodiment of the thermally conductive substrate of this application;

[0045] Figure 3 This is a schematic flowchart of one embodiment of the preparation method of the liquid metal graphene thermal conductive pad of this application;

[0046] Figure 4 This is a schematic diagram of the product structure corresponding to one embodiment of the preparation method of the liquid metal graphene thermal pad of this application.

[0047] Explanation of key figure labels:

[0048] Thermally conductive substrate 10; first graphene foam layer 100; composite layer 101; second graphene foam layer 1011; low-melting-point liquid metal layer 1012;

[0049] High-melting-point liquid metal layer 20;

[0050] Graphene foam 30;

[0051] Low melting point liquid metal sheet 40. Detailed Implementation

[0052] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions in the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.

[0053] The graphene powder on the surface of existing graphene thermal pads is prone to falling off, which can easily lead to risks such as short circuits and reduced insulation performance. In addition, the anisotropy is significant, and the tensile strength perpendicular to the graphene sheet arrangement direction is extremely low, making it easy to crack and break, and the service life is difficult to guarantee.

[0054] Currently, liquid metal is combined with graphene thermal pads to improve vertical thermal conductivity. However, the interfacial bonding between graphene and liquid metal is unreliable. Directly penetrating liquid metal into the pores inside graphene can easily lead to the exposure of low-melting-point liquid metal on the pad surface, causing electrochemical corrosion and metal embrittlement.

[0055] To address the aforementioned issues, the applicant has developed a novel liquid metal graphene thermally conductive pad. This pad significantly improves the mechanical properties of the pad in all directions, ensures the bonding strength between the liquid metal and graphite, and avoids electrochemical corrosion and metal embrittlement caused by exposure to low-melting-point liquid metal. This allows the pad to achieve a balance of high thermal conductivity, excellent mechanical strength, reliable interfacial bonding, and leak-proof and corrosion-resistant properties.

[0056] Specifically, please refer to Figure 1 , Figure 1 This is a schematic diagram of one embodiment of the liquid metal graphene thermal conductive pad of this application.

[0057] like Figure 1 As shown, the thermal pad includes a thermally conductive substrate 10 and a high-melting-point liquid metal layer 20 covering and bonded to both sides of the thermally conductive substrate 10 in the thickness direction.

[0058] The high-melting-point liquid metal layer 20 is located on the surface of the pad. It is used to directly contact electronic components such as chips and heat sinks to achieve interface heat conduction and avoid electrochemical corrosion caused by the melting of liquid metal.

[0059] In one embodiment, the melting point of the high-melting-point liquid metal layer 20 can be 115~125°C, which is much higher than the operating temperature of electronic components.

[0060] Specifically, the high-melting-point liquid metal layer 20 can be any liquid metal that meets the melting point requirement, such as indium-tin eutectic alloy, etc., all of which can achieve the effect of this embodiment.

[0061] For further details, please refer to Figure 2 , Figure 2 This is a schematic diagram of one embodiment of the thermally conductive substrate 10 of this application. Figure 2 As shown, the thermally conductive substrate 10 includes a first graphene foam layer 100 and a composite layer 101 that are alternately stacked along the first direction x. The composite layer 101 includes a second graphene foam layer 1011 and a low-melting-point liquid metal layer 1012 that are alternately stacked along the second direction y.

[0062] The first graphene foam layer 100, the second graphene foam layer 1011, and the low-melting-point liquid metal layer 1012 are bonded together by curing with a silicone matrix. The silicone matrix fills the internal pores and interlayer gaps of the first graphene foam layer 100 and the second graphene foam layer 1011.

[0063] In one embodiment, the melting point of the low-melting-point liquid metal layer 1012 can be 60~70°C.

[0064] Specifically, the low-melting-point liquid metal layer 1012 can be any liquid metal that meets the melting point requirement, such as bismuth indium tin eutectic alloy, etc., all of which can achieve the effect of this embodiment.

[0065] Based on the above solution, in the first aspect, the thermal pad includes a first graphene foam layer 100 stacked along the first direction x and a second graphene foam layer 1011 stacked along the second direction y. The graphene foam is filled with and cured with silicone, thereby forming a crisscrossing multi-dimensional three-dimensional support network, which enables the pad to have excellent mechanical strength in all directions in the plane, solving the problem of extremely low mechanical strength of traditional graphene thermal pads in the direction perpendicular to the arrangement of the layers.

[0066] Secondly, the low-melting-point liquid metal layer 1012 of the thermal pad of this application is encapsulated inside the thermally conductive substrate 10 and stacked with the second graphene foam layer 1011 in a direction perpendicular to the thickness direction to form a composite layer 101, which effectively avoids the electrochemical corrosion problem caused by leakage of low-melting-point liquid metal. At the same time, the low-melting-point liquid metal layer 1012 encapsulated inside can form vertical thermal conduction channels at various parts of the thermal pad, effectively ensuring the vertical thermal conductivity of the thermal pad.

[0067] Thirdly, the surface of the thermal pad of this application is in contact with electronic components such as chips and heat sinks through a high melting point liquid metal layer 20, and the graphene foam is filled with and solidified with a silicone matrix, which effectively avoids the problem of short circuit caused by graphene powder falling off, and effectively ensures the thermal conductivity of the thermal pad.

[0068] Fourthly, this application significantly improves the bonding strength between the low-melting-point liquid metal and the graphene foam by curing and bonding the first graphene foam layer 100, the second graphene foam layer 1011 and the low-melting-point liquid metal layer 1012 with a silicone substrate, avoiding the problem of increased interfacial thermal resistance caused by the delamination of liquid metal and graphite, and helping to improve service life and thermal conductivity.

[0069] In this embodiment, the first direction x and the second direction y are perpendicular; in other embodiments, the first direction x and the second direction y may not be perpendicular, for example, they may form other angles such as 30° or 60°, which can be adjusted according to actual needs, and all can achieve the effect of this embodiment.

[0070] Furthermore, such as Figure 1 As shown, in this embodiment, the outermost part of the thermally conductive substrate 10 in the first direction x is the first graphene foam layer 100; the outermost part of the composite layer 101 in the second direction y is the second graphene foam layer 1011.

[0071] Based on the above solution, the low-melting-point liquid metal is prevented from being directly exposed to the surface of the thermal pad, allowing the low-melting-point liquid metal to be completely encapsulated inside the thermal pad, thus avoiding the risk of leakage.

[0072] In one embodiment, the thickness of the thermally conductive substrate 10 can be 180~220μm, and the thickness of the high-melting-point liquid metal layer 20 can be 20~50μm.

[0073] Based on the above scheme, thermal conductivity, sealing reliability and mechanical properties are achieved, while avoiding the impact of an excessively thick high-melting-point liquid metal layer 20 on the overall compression performance.

[0074] In the first direction x, the first graphene foam layer 100 has an extension length of 380~420μm, and the composite layer 101 has an extension length of 80~120μm.

[0075] Based on the above scheme, the first graphene foam layer 100 with a diameter of 380~420μm serves as the main supporting skeleton, which can provide sufficient structural rigidity and significantly improve the tensile strength and bending resistance in this direction; the composite layer 101 with a diameter of 80~120μm serves as a high thermal conductivity unit, forming a continuous and uniform thermal conductivity path to quickly dissipate local heat.

[0076] In the second direction y, the extension length of the second graphene foam layer 1011 is 380~420μm, and the extension length of the low-melting-point liquid metal layer 1012 is 80~220μm.

[0077] Based on the above scheme, within this size range, the low-melting-point liquid metal is fully confined within the graphene pores and the silicone matrix, which not only ensures the interfacial bonding strength but also restricts the free migration of the liquid metal. Under long-term thermal cycling, it can still maintain stable thermal conductivity and structural reliability, while avoiding excessive low-melting-point liquid metal from affecting the compression performance.

[0078] Furthermore, in one embodiment, the silicone matrix can be obtained by curing a silicone curing liquid comprising the following components: vinyl silicone oil, end-hydrogen silicone oil, side-hydrogen silicone oil, carboxyl silicone oil, platinum-coated catalyst, and titanate coupling agent.

[0079] In the components of the above-mentioned silicone curing liquid, vinyl silicone oil, end-hydrogen silicone oil, side-hydrogen silicone oil, and carboxyl silicone oil can undergo an addition curing reaction under the action of a platinum catalyst to obtain silicone.

[0080] Among them, vinyl silicone oil is the basic main component. The vinyl functional group can undergo a hydrosilylation reaction with the Si-H bond of the terminal hydrogen-containing silicone oil and the side hydrogen-containing silicone oil to form a continuous three-dimensional cross-linked network, which improves the mechanical reliability and compression resilience of the overall thermal pad.

[0081] Liquid metal surfaces typically have an oxide layer. The carboxyl functional groups on the molecular chain of carboxyl silicone oil can react chemically with the oxide layer on the surface of liquid metal to form chemical bonds, thereby increasing the bonding strength between silicone and liquid metal. This effectively avoids the problem of separation at the interface between graphene and liquid metal, and improves the stability and thermal conductivity of the thermal pad.

[0082] Meanwhile, the organosilicon backbone of carboxyl silicone oil has excellent compatibility with the vinyl silicone oil system, can be uniformly dispersed in the curing liquid, and can participate in hydrosilylation reaction to embed into the cross-linking network, ensuring the long-term stability of the interface bonding.

[0083] The platinum-coated catalyst is a platinum catalyst encapsulated in a phase change material, so that the platinum catalyst can be released when the phase change material melts and catalyze the addition curing reaction of silicone oil.

[0084] By coating the catalyst with platinum, the curing reaction of the silicone curing liquid can be precisely controlled, avoiding the impact of silicone curing on the melting and penetration of low-melting-point liquid metal, which helps to further improve the bonding strength between the low-melting-point liquid metal and graphene.

[0085] In one embodiment, the phase change material may specifically be paraffin wax, the melting point of the phase change material may specifically be 78~82°C, and the platinum catalyst coated in the phase change material may specifically be a Karstedt platinum catalyst.

[0086] Paraffin wax has a certain strength, so it does not crack during stirring and mixing, and melts when it reaches the phase change material, stably releasing the platinum catalyst.

[0087] Titanate coupling agents are chelates formed with titanium atoms as the coordination core. They have similar metallic polarity to liquid metal and can tightly bind to the surface of liquid metal through coordination. The organic functional groups at the other end of the molecule can interact with the active groups of silicone oil segments to construct a molecular bridging pathway between liquid metal, coupling agent, and silicone oil, further enhancing the interfacial bonding strength between silicone and liquid metal and improving the service life and operational stability of thermal pads.

[0088] In addition, free water is generated during the reaction between the carboxyl functional groups of carboxyl silicone oil and the oxide layer on the surface of liquid metal. Some of the free water can be volatilized during subsequent heating. At the same time, the titanate coupling agent can also absorb the free water, so as to avoid the free water residue affecting the product performance.

[0089] In one embodiment, the titanate coupling agent may specifically be titanate coupling agent NDZ-201, namely isopropyl tris(dioctylpyrophosphate) titanate.

[0090] Based on the above scheme, by introducing carboxyl silicone oil and titanate coupling agent into the components of silicone curing liquid, the interfacial bonding strength between graphene and liquid metal is effectively improved, thereby increasing the service life and working stability of the thermal pad. By introducing a platinum-coated catalyst to precisely control curing, it helps to improve the bonding strength between low-melting-point liquid metal and graphene.

[0091] Furthermore, in one embodiment, the silicone curing liquid may specifically include the following components by weight: 78-82 parts of vinyl silicone oil, 8-12 parts of end-hydrogen silicone oil, 3-7 parts of side-hydrogen silicone oil, 2-4 parts of carboxyl silicone oil, 0.3-0.6 parts of platinum-coated catalyst, and 1-2 parts of titanate coupling agent.

[0092] Based on the above scheme, excessive carboxylated silicone oil is avoided, which would lead to excessive consumption of the liquid metal oxide layer, causing the carboxylated silicone oil to react directly with the liquid metal to produce hydrogen gas, resulting in bubbles at the bonding interface and affecting the bonding strength. In addition, excessive reaction of carboxylated silicone oil would also be avoided to produce excessive free water. At the same time, sufficient carboxylated silicone oil is ensured to improve the bonding stability between silicone and liquid metal.

[0093] This application also provides a method for preparing a liquid metal graphene thermal pad according to any of the above embodiments. Please refer to [link to relevant documentation]. Figure 3 and Figure 4 , Figure 3 This is a schematic flowchart of one embodiment of the preparation method of the liquid metal graphene thermal conductive pad of this application. Figure 4 This is a schematic diagram of the product structure corresponding to one embodiment of the preparation method of the liquid metal graphene thermal pad of this application.

[0094] like Figure 3 As shown, the preparation method includes:

[0095] S101. Graphene foam and low-melting-point liquid metal sheets are alternately stacked in a mold.

[0096] In one embodiment, the density of the graphene foam can be 0.15~0.25 g / cm³. 3 This ensures that it has enough pores to fill the silicone.

[0097] Specifically, see Figure 4 In section A, graphene foam 30 and low-melting-point liquid metal sheet 40 are stacked alternately along the second direction y, with graphene foam 30 on the outermost side to avoid the subsequent low-melting-point liquid metal being exposed on the outer surface of the thermal pad.

[0098] S102. Infiltrate the graphene foam with silicone curing liquid.

[0099] In one embodiment, the method of infiltrating the silicone curing liquid into the graphene foam can be specifically as follows:

[0100] The mold is immersed in silicone curing liquid, and the inside of the mold is vacuumed to allow the graphene foam to fully absorb the silicone curing liquid.

[0101] S103. Heat the mold to melt the low-melting-point liquid metal sheet and solidify the silicone curing liquid to form a silicone matrix, thereby obtaining the first graphene liquid metal block.

[0102] Specifically, the steps for heating the mold can be as follows:

[0103] The mold is heated to a first temperature, which melts the low-melting-point liquid metal sheet and partially penetrates into the adjacent graphene foam. The first temperature is lower than the melting point of the phase change material.

[0104] The mold is heated to a second temperature, which causes the silicone curing liquid to solidify and form a silicone matrix. The second temperature is higher than the melting point of the phase change material.

[0105] At the first temperature, the molten low-melting-point liquid metal can partially penetrate into the graphene foam, while the platinum catalyst remains coated. The silicone curing liquid remains in a liquid state to avoid affecting the penetration of the low-melting-point liquid metal. At the same time, the low-melting-point liquid metal can also react and connect with the carboxyl silicone oil and titanate coupling agent in the silicone curing liquid.

[0106] At the second temperature, the phase change material coated on the platinum catalyst melts, and the platinum catalyst is released into the system and catalyzes the addition curing reaction to form a silicone matrix.

[0107] By combining the above-mentioned staged heating method with platinum-coated catalyst, the bonding strength between liquid metal and graphene and silicone interfaces is significantly improved, thereby enhancing the service life and operational stability of the thermal pad.

[0108] S104. Take out the first graphene liquid metal block and cut it along its stacking direction to obtain a graphene liquid metal sheet.

[0109] See also Figure 4 After cutting, graphene liquid metal sheet is obtained, which is composed of graphene foam 30 and low melting point liquid metal sheet 40 stacked sequentially along the second direction y.

[0110] S105. Graphene foam and graphene liquid metal sheets are alternately stacked in the mold.

[0111] See also Figure 4 In section C, graphene foam 30 and graphene liquid metal sheets are stacked alternately along the first direction x, with graphene foam 30 on the outermost side to prevent low-melting-point liquid metal from being exposed on the surface of the thermal pad.

[0112] S106. Infiltrate the graphene foam with silicone curing liquid.

[0113] For details on the specific method, please refer to step S102, which will not be repeated here.

[0114] S107. Heat the mold to melt the low-melting-point liquid metal sheet and solidify the silicone curing liquid to form a silicone matrix, thereby obtaining the second graphene liquid metal block.

[0115] For details on the specific method, please refer to step S103, which will not be repeated here.

[0116] S108. Take out the second graphene liquid metal block and cut it along its stacking direction to obtain the thermally conductive substrate.

[0117] See also Figure 4 D, after being cut, yields a thermally conductive substrate 10, which includes a first graphene foam layer 100 and a composite layer 101 stacked alternately along the first direction x. The composite layer 101 includes a second graphene foam layer 1011 and a low-melting-point liquid metal layer 1012 stacked alternately along the second direction y.

[0118] S109. High-melting-point liquid metal sheets are covered on both sides of the thermally conductive substrate in the thickness direction. The high-melting-point liquid metal sheets are heated to melt, pressed together, and then cooled to obtain a liquid metal graphene thermally conductive pad.

[0119] See also Figure 4 In section E, the heating temperature is greater than or equal to the melting point of the high-melting-point liquid metal sheet, so that some of the high-melting-point liquid metal can penetrate into the heat-conducting matrix and improve the interfacial bonding strength.

[0120] Based on the preparation methods described above, by performing two silicone curing processes and two cutting processes, and by using a staged gradient heating method during each silicone curing process, the low-melting-point liquid metal can be partially infiltrated into the pore structure of the graphene foam to form a mechanical anchor, while ensuring uniform cross-linking and curing of the silicone matrix. Ultimately, a uniformly distributed, multi-directional, and continuously interconnected graphene-liquid metal composite thermal conductive network and a three-dimensional mechanical support system are constructed inside the gasket, which significantly improves the interfacial bonding strength, the anisotropic mechanical properties of the gasket, and the compression and rebound characteristics. At the same time, the low-melting-point liquid metal is encapsulated inside, effectively reducing the risk of low-melting-point liquid metal leakage and device corrosion.

[0121] The beneficial effects of the technical solution of this application will be further described in detail below with reference to specific embodiments.

[0122] Example 1:

[0123] A thermally conductive pad is prepared by the following steps:

[0124] 1. Select a density of 0.2 g / cm³ 3 Graphene foam with a thickness of 400μm is cut into standard length and width to obtain standard sheets. 220 standard sheets and 219 low melting point liquid gold sheets with a thickness of 100μm are stacked alternately and placed in a fixed thickness mold. The upper and lower surfaces are both standard sheets.

[0125] 2. Immerse the mold in the silicone curing liquid and vacuum the inside of the mold to allow the graphene foam to fully absorb the silicone curing liquid. Maintain the vacuum state for 5 minutes.

[0126] The silicone curing liquid has the following mass fractions: vinyl silicone oil (VS500, Ambia) 80%, end-hydrogen silicone oil (CE-500, Ambia) 10%, side-hydrogen silicone oil (XL-12, Ambia) 5%, carboxyl silicone oil (IOTA 2520, IOTA) 3%, platinum-coated catalyst (KJC-PT5000D, Kejunchi) 0.5%, and titanate coupling agent (NDZ-201, Jessica Chemicals) 1.5%.

[0127] 3. Remove the mold and heat it in a 70℃ oven for 60 minutes;

[0128] 4. Further heat to 125℃ and maintain for 30 minutes;

[0129] 5. Disassemble the mold, take out the first graphene liquid metal block, cool it to room temperature, and then cut it along the stacking direction with an ultrasonic cutter to obtain a 100μm thick graphene liquid metal sheet.

[0130] 6. Stack 220 standard sheets and 219 graphene liquid metal sheets alternately and place them into a thickness-fixed mold, wherein the upper and lower surfaces are both standard sheets;

[0131] 7. Repeat steps 2-4 above, disassemble the mold, take out the second graphene liquid metal block, cool it to room temperature, and then cut it along the stacking direction with an ultrasonic cutter to obtain a 200μm thick thermally conductive substrate.

[0132] 8. Cover the upper and lower surfaces of the thermally conductive substrate with 25μm thick high-melting-point liquid metal sheets, heat to 120℃, press and bond them together, and then cool to room temperature to obtain a thermally conductive pad.

[0133] Example 2:

[0134] A thermally conductive pad, prepared in a manner basically the same as in Example 1, except that:

[0135] The thickness of the low-melting-point liquid gold sheet is 200μm. In step 1, 183 standard sheets and 182 low-melting-point liquid gold sheets are stacked alternately.

[0136] Example 3:

[0137] A thermally conductive pad, prepared in a manner basically the same as in Example 1, except that:

[0138] The thickness of the high-melting-point liquid metal sheet is 40 μm.

[0139] Comparative Examples 1 to 7:

[0140] A thermally conductive pad, prepared in a manner basically the same as in Example 1, except that:

[0141] The components of silicone curing liquid vary; please refer to the table below for details.

[0142]

[0143] Example of results:

[0144] The thermally conductive pads of Examples 1 to 3 and Comparative Examples 1 to 7 were tested for tensile strength in the width direction, thermal conductivity in the vertical direction, and compressibility in the thickness direction at 40 psi, and the following data were obtained.

[0145]

[0146] As shown in the data above, the tensile strength of the thermally conductive pads in Examples 1 to 3 all reach 0.50 MPa or above, and the vertical thermal conductivity reaches 180 W or above. Moreover, after compression under 40 psi pressure, there is no interlayer cracking or liquid metal seepage, and the overall structure remains intact. It achieves synergistic improvement in mechanical strength, thermal conductivity and compression reliability, effectively solving the defects of performance imbalance and insufficient reliability of existing technical solutions.

[0147] Specifically, compared with Example 1 and Comparative Example 1, the silicone curing liquid of Comparative Example 1 did not contain a titanate coupling agent, and relied solely on carboxylated silicone oil to form a chemical bond with the oxide layer on the surface of liquid metal. Its tensile strength was significantly lower than that of Example 1, and it cracked after compression under 40 psi pressure. At the same time, its vertical thermal conductivity was significantly lower than that of Example 1, indicating poor interfacial bonding between graphene and liquid metal.

[0148] Compared with Example 1 and Comparative Examples 2 and 4, the silicone curing liquid of Comparative Examples 2 and 4 did not contain carboxyl silicone oil, which could not achieve chemical bonding between liquid metal and silicone, resulting in a more significant decrease in tensile strength and a greater decrease in vertical thermal conductivity, and cracking after compression under 40 psi pressure.

[0149] Compared with Example 1 and Comparative Example 3, the silicone curing liquid of Comparative Example 3 did not contain carboxyl silicone oil, so it could not achieve chemical bonding between liquid metal and silicone. The interfacial bonding strength was low, and the vertical thermal conductivity was significantly lower than that of Example 1. At the same time, the side hydrogen-containing silicone oil content of Comparative Example 3 was increased compared with Example 1, which led to a significant increase in silicone strength. Therefore, it had a large tensile strength, but the material hardness was high and the compression ratio was low, only 10%, which could not meet the requirements.

[0150] Compared with Example 1 and Comparative Examples 5 and 6, the silicone curing liquid of Comparative Examples 5 and 6 contained excessive carboxyl silicone oil, which caused the oxide layer on the surface of the liquid metal to be completely destroyed. During the thermal conductivity test, when heated to 80°C, low-melting-point liquid metal precipitated and leaked.

[0151] Compared with Example 1, Comparative Example 7 did not add carboxyl silicone oil and titanate coupling agent to the silicone curing liquid of Comparative Example 7. The tensile strength of the thermal pad of Example 1 was increased by 10 times compared with Comparative Example 7. This was mainly due to the chemical bonding between carboxyl silicone oil and the oxide layer on the liquid gold surface, and the bridging effect of titanate coupling agent on liquid gold-silicone, which significantly improved the interfacial bonding strength.

[0152] Comparing Example 1 and Example 2, the thickness of the low-melting-point liquid metal sheet in Example 2 is greater than that in Example 1, which results in the product of Example 2 having more low-melting-point liquid metal running through it from top to bottom, significantly improving tensile strength and slightly improving thermal conductivity. However, due to the higher proportion of liquid metal, the overall compressibility is reduced.

[0153] Compared with Example 1 and Example 3, the thickness of the high melting point liquid metal sheet in Example 3 is greater than that in Example 1, resulting in a significant increase in overall tensile strength. Since the low melting point liquid metal running through the entire structure remains unchanged, the thermal conductivity is slightly improved, while the compressibility is reduced.

[0154] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0155] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A liquid metal graphene thermal conductive pad, characterized in that, It includes a thermally conductive substrate and a high-melting-point liquid metal layer covering and bonded to both sides of the thermally conductive substrate in the thickness direction; The thermally conductive substrate includes a first graphene foam layer and a composite layer that are alternately stacked along a first direction. The composite layer includes a second graphene foam layer and a low-melting-point liquid metal layer that are alternately stacked along a second direction. The first graphene foam layer, the second graphene foam layer, and the low-melting-point liquid metal layer are bonded together by curing with a silicone matrix. The silicone matrix fills the internal pores and interlayer gaps of the first graphene foam layer and the second graphene foam layer. Wherein, the first direction is perpendicular to the thickness direction of the thermally conductive substrate, the second direction is perpendicular to the thickness direction of the thermally conductive substrate, and an angle is formed between the first direction and the second direction.

2. The liquid metal graphene thermal pad according to claim 1, characterized in that, The high-melting-point liquid metal layer has a melting point of 115~125℃; and / or, The melting point of the low-melting-point liquid metal layer is 60~70℃.

3. The liquid metal graphene thermal pad according to claim 1, characterized in that, The outermost part of the thermally conductive substrate in the first direction is the first graphene foam layer; and / or, The outermost part of the second direction of the composite layer is the second graphene foam layer.

4. The liquid metal graphene thermal pad according to claim 1, characterized in that, The thickness of the thermally conductive substrate is 180~220μm, and the thickness of the high-melting-point liquid metal layer is 20~50μm; And / or, In the first direction, the first graphene foam layer has an extension length of 380~420μm, and the composite layer has an extension length of 80~120μm; and / or, In the second direction, the extension length of the second graphene foam layer is 380~420μm, and the extension length of the low-melting-point liquid metal layer is 80~220μm.

5. A method for preparing a liquid metal graphene thermal conductive pad according to any one of claims 1 to 4, characterized in that, include: Graphene foam and low-melting-point liquid metal sheets are alternately stacked in a mold; The silicone curing liquid is infiltrated into the graphene foam; The mold is heated to melt the low-melting-point liquid metal sheet and to solidify the silicone curing liquid to form a silicone matrix, thereby obtaining a first graphene liquid metal block; The first graphene liquid metal block was removed and cut along its stacking direction to obtain a graphene liquid metal sheet; Graphene foam and the graphene liquid metal sheet are alternately stacked in a mold; The silicone curing liquid is infiltrated into the graphene foam; The mold is heated to melt the low-melting-point liquid metal sheet and to solidify the silicone curing liquid to form a silicone matrix, thereby obtaining a second graphene liquid metal block; The second graphene liquid metal block is removed and cut along its stacking direction to obtain the thermally conductive substrate; High-melting-point liquid metal sheets are covered on both sides of the thermally conductive substrate in the thickness direction. The high-melting-point liquid metal sheets are heated to melt, pressed together, and then cooled to obtain the liquid metal graphene thermally conductive pad.

6. The preparation method according to claim 5, characterized in that, The silicone curing liquid comprises the following components: vinyl silicone oil, end-hydrogen silicone oil, side-hydrogen silicone oil, carboxyl silicone oil, platinum-coated catalyst, and titanate coupling agent; The platinum-coated catalyst is a platinum catalyst encapsulated in a phase change material, so that the platinum catalyst can be released when the phase change material melts and catalyze the addition curing reaction of silicone oil.

7. The preparation method according to claim 6, characterized in that, The step of heating the mold includes: The mold is heated to a first temperature, which melts the low-melting-point liquid metal sheet and partially penetrates into the adjacent graphene foam. The first temperature is lower than the melting point of the phase change material. The mold is heated to a second temperature to solidify the silicone curing liquid and form a silicone matrix. The second temperature is greater than the melting point of the phase change material.

8. The preparation method according to claim 7, characterized in that, The phase change material has a melting point of 78~82℃, the first temperature is 65~75℃, and the second temperature is 100~130℃; and / or, The phase change material is paraffin.

9. The preparation method according to claim 6, characterized in that, The silicone curing liquid comprises the following components by weight: 78-82 parts vinyl silicone oil, 8-12 parts end-hydrogen silicone oil, 3-7 parts side-hydrogen silicone oil, 2-4 parts carboxyl silicone oil, 0.3-0.6 parts platinum-coated catalyst, and 1-2 parts titanate coupling agent.

10. The preparation method according to claim 5, characterized in that, The step of infiltrating the silicone curing liquid into the graphene foam includes: immersing the mold in the silicone curing liquid, and performing a vacuum treatment inside the mold to allow the graphene foam to fully absorb the silicone curing liquid; and / or, The density of the graphene foam is 0.15~0.25 g / cm³. 3 .